2018
DOI: 10.1016/j.neuroimage.2018.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Model-free and model-based reward prediction errors in EEG

Abstract: Learning theorists posit two reinforcement learning systems: model-free and model-based. Model-based learning incorporates knowledge about structure and contingencies in the world to assign candidate actions with an expected value. Model-free learning is ignorant of the world's structure; instead, actions hold a value based on prior reinforcement, with this value updated by expectancy violation in the form of a reward prediction error. Because they use such different learning mechanisms, it has been previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 64 publications
0
41
1
Order By: Relevance
“…Previous EEG studies of the two-step task (Eppinger et al, 2017;Sambrook et al, 2018;Shahnazian et al, 2019) showed that the P300 was associated with state transitions. However, the inconsistent direction on the effects raises doubt as to how these differences should be interpreted.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Previous EEG studies of the two-step task (Eppinger et al, 2017;Sambrook et al, 2018;Shahnazian et al, 2019) showed that the P300 was associated with state transitions. However, the inconsistent direction on the effects raises doubt as to how these differences should be interpreted.…”
Section: Discussionmentioning
confidence: 96%
“…The P300 or P3b has well-established sensitivity to stimulus probability, exhibiting larger peak amplitudes for less probable stimuli (Polich & Margala, 1997). Prior research in healthy humans thus hypothesised that the P300 may be a marker of sensitivity to state transitions on the two-step task, though these studies have yielded inconsistent results, with some finding greater P300 amplitudes for rare versus common transitions (Sambrook, Hardwick, Wills, & Goslin, 2018;Shahnazian, Ribas-Fernandes, & Holroyd, 2019) and one finding the opposite (Eppinger, Walter, & Li, 2017). Here, we examined the second stage stimulus-locked P300 and found a significant main effect of transition type (β = 0.15, SE = 0.07, p = 0.03), consistent with Sambrook et al (2018) and Shahnazian et al (2019) whereby greater P300 amplitude was observed after rare versus common transitions (Figure 3).…”
Section: (C) Rt Difference Between Transition Type (Rt-transmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in contrast to Experiment 1, because this experiment involved rewards, it allowed for a possible confound between SPEs and RPEs. Note that although the concurrent effects of RPEs and SPEs can be disentangled using advanced modeling approaches (see Sambrook, Hardwick, Wills, & Goslin, 2018), such approaches require the application of a linear regression on multiple variables (in the present case, SPE, RPE and the ongoing EEG), and so have relatively limited statistical power.…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that these two sources of information—past experience and internal models—improve decision making via two different learning mechanisms called model-free learning and model-based learning (Daw & O’Doherty, 2014 ; Dayan & Berridge, 2014 ; O’Doherty, Cockburn, & Pauli, 2017 ). Despite the long held assumption of computationally dissociable learning mechanisms, recent literature suggests an integration of model-free and model-based information at the level of feedback processing (Daw, Gershman, Seymour, Dayan, & Dolan, 2011 ; Sambrook, Hardwick, Wills, & Goslin, 2018 ), and this integration might be sensitive to the structure of the environment as represented by an internal model (Eppinger, Walter, & Li, 2017 ; Lee, Shimojo, & O’Doherty, 2014 ). We ask how different environmental structures and thus internal models exert influence on both behavioral and neural aspects of feedback evaluation.…”
Section: Introductionmentioning
confidence: 99%